Enhanced Magnetic Properties of Co1−xMnxFe2O4 Nanoparticles - Adam Szatmari; Rareș Bortnic; Roman Atanasov; Lucian Barbu-Tudoran; Fran Nekvapil; Roxana Dudric; Romulus Tetean (Applied Sciences)
Co1−xMnxFe2O4 nanoparticles (0 ≤ x ≤ 1) have been prepared via the hydrothermal method. The prepared samples were studied using X-ray diffraction measurements (XRD), transmission electron microscopy (TEM), Raman spectroscopy, and magnetic measurements. All studied samples were found to be single phases and to have a cubic Fd-3m structure. The average crystalline sizes are between 7.8 and 15 nm. EDS analysis confirmed the presence of cobalt, manganese, iron, and oxygen in all prepared samples. It was found by Raman spectroscopy that Fe3+ would be placed on octahedral sites while Fe2+ would, in turn, be displaced to tetrahedral sites while Mn ions will be placed on both sites. Both Mn2+ and Mn4+ are present in studied ferrites. The experimental saturation magnetizations for doped samples are much higher when compared with previous reports, reaching values between 3.71 and 6.7 μB/f.u. The doping with Mn in nanocrystalline cobalt ferrite enhanced the magnetic properties due to changes in the cation distribution between the two sublattices. The higher magnetic moments are explained by the presence of Mn4+ ions located preferentially on tetrahedral sites while Mn2+ prefer octahedral sites, and by the high quality and crystallinity of our samples the nanoparticles being almost monodomain. Large values of the coercive field were found at 4.2 K while the hysteresis is almost absent in all investigated samples at room temperature.